EFFECT OF SESAME (SESAMUM-INDICUM L) ON NEST DEVELOPMENT OF ATTA-SEXDENS-RUBROPILOSA FOREL (HYM, FORMICIDAE) - Bueno, O. C.; Hebling, MJA; Silva, O. A.; Matenhauer, AMC (Blackwell Wissenschafts Verlag Gmbh, 1995)
The present study showed a strong deleterious effect on leaf-cutting ant Atta sexdens rubiopilosa nests supplied exclusively with sesame (Sesamum indicum) leaves in the laboratory. Sesame leaves were initially attractive to workers and later became antifeedant. Eucaliptus alba and Hibiscus rosa-sinensis leaves were used as control.